ASPEK SOSIAL EKONOMI DAN BUDAYA DALAM TINGKAT KESEJAHTERAAN MASYARAKAT TENGANAN PEGRINGSINGAN - Parwita, Gde Bayu Surya (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2013)
The aim of this research is to determine the level of public welfare in the village of Tenganan Pegringsingan review of the aspect of social and economic and  knowing the role of customary institution on the public welfare in the village of Tenganan Pegringsingan. Location of this research is a village located in Tenganan Pegringsingan sub-district Manggis district Karangasem. Regional Gross Domestic Product  (GDP) per capita and human development index in the county of this is the lowest in the Province of Bali. Villagers of Tenganan Pegringsingan chosen as the object of this research because of the consistency of them against the customs and culture in the middle of globalization are traditional pattern of life has shifted into modern. To answer the problems until research, can reach its destination engineering analysis will be used either quantitative or qualitative. The result showed in flattened, society wage in Tenganan Pegringsingan is lower than Karangasem, according to a district but for the community this income it has been able to meet the needs of their lives. Customary very institution plays role in the public welfare village Tenganan Pegringsingan. This is because high intervening customary in the management of assets village then capable of being restored fair and equitable to the public.